On a Bilingual Copto-Arabic Manuscript of 4 Ezra and the Reception of this Pseudepigraphon in Coptic Literature - Suciu, Alin (Journal for the study of the pseudepigrapha, 2015)
The text of 4 Ezra has survived in many ancient languages. Among these, the Sahidic Coptic version is the most poorly attested. The focus of this study is to introduce a new Sahidic fragment of this Jewish pseudepigraphon, which is preserved in a bilingual Copto-Arabic manuscript from the Monastery of Apa Shenoute. This hitherto unknown fragment is datable to the late fourteenth or early fifteenth century. The article provides an edition of the newly identified fragment, together with a paleographical description, an analysis of the text, and a survey of the relevant sources pertaining to the reception of 4 Ezra in Coptic and Copto-Arabic literature.